AN ANALYSIS OF DESCRIPTIVE TEXT IN ENGLISH TEXTBOOK USING TRANSITIVITY SYSTEM (A CASE STUDY OF READING PASSAGES) - Shafira Khairina Anggun (Journal of English and Education, 2016)
The main focus of the study is to investigate to what extent the descriptive texts in English textbook meet its criteria in terms of purposes, schematic structures and linguistic features. A qualitative case study method with document analysis technique is employed as the method of the study. The study also applied Systemic Functional Linguistics framework proposed mainly by M.A.K. Halliday, yet the study had focused on Transitivity system in analyzing descriptive texts. The prime data of the study were four descriptive texts of reading passages from four different chapters of an English textbook which have implemented 2013 Curriculum. The data analysis was done by examining social purposes, schematic structures and linguistics features (mainly Transitivity system). The findings showed that in terms of social purpose, three out of four descriptive texts met the purpose of descriptive text. In terms of schematic structure, one text met the criteria as descriptive text included personal comment; two texts met the criteria of descriptive text but did not include personal comment; and the last one did not meet the criteria of descriptive text. Moreover, in terms of linguistic features, only two of four descriptive texts had closely followed the linguistic features of descriptive text. However, it can be concluded that some descriptive texts in the textbook entitled “Bahasa Inggris for Senior High School Grade X” were unsatisfactory in which they were not satisfy the criteria of descriptive text.